Analisis Ekonomi Sapi Potong Pola Gaduhan: Studi Kasus di Desa Slorok, Kecamatan Kromengan, Kabupaten Malang - Tribudi, Yuli Arif; Ristyawan, Mochammad Ridwan (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2017)
The current study was done in March 2016 by involving the cattle farmers from Slorok village, Kromengansubdistrict, Malang. The objective of this study was to investigate revenue of cattle sharing system and toanalyze its contribution on the farmer family's income. There is 18 farmers who used sharing system, wasselected by total sampling method. Primary data was collected by through survey and interview. The secondarydata was gained from institutions and related sources. Data analysis used in this study was income analysis ofcattle farmers (who used sharing system). The result showed that cattle farmer's income at Slorok was Rp.3.259.853/beef/year which was come from cattle sharing income.